Como os agentes comunitários de saúde se comunicam com as pessoas com diabetes na perspectiva da alimentação saudável? - Ferreira, Mariana Gabriele de Souza (2024)
Considered a severe public health problem, Diabetes Mellitus (DM) is a chronic disease with social and financial implications for everyone involved. The role of Community Health Workers (CHW) in this context is to encourage changes in the lifestyle of people with DM. Therefore, communication skills are presented as facilitators of this challenging task, and one of the approaches that stands out is Motivational Interviewing (MI). This study aims to analyze how CHWs communicate with people with DM based on the MI framework, focusing on engagement in self-care and healthy eating. To this end, exploratory qualitative research with a phenomenological basis was carried out with CHWs working in a city in the Brazilian Northeast. A questionnaire and semi-structured interview were used to collect data, with the data saturation criterion being the means to determine the sample size. The interviews were recorded, transcribed, and analyzed using the Thematic-categorical Content Analysis technique. All 102 CHWs working in the municipality were invited to participate; 69 completed the questionnaire, and nine were selected for the interview, considering the diversity and homogeneity of the participants. The Municipal Health Department and CEP-UFSCar approved the research. It was possible to identify that the CHWs are sensitive to the socioeconomic reality of the community, are concerned with promoting the well-being of the people in their territory, and aim to do a good job. CHWs communicate with people with DM using some of the premises of MI, such as the compassionate and partner approach. However, they do so intuitively. In most of the interviews, they employ vertical and persuasive communication, disregarding food's sociocultural and affective aspects, which goes against what Primary Health Care and the Food Guide for the Brazilian Population recommends. The CHWs claim to have little knowledge about DM and its forms of treatment, demonstrating insecurity in their conduct and several doubts when speaking about the subject. They believe that DM negatively impacts people's lives and that they do not give due importance to their self-care, especially concerning nutrition. It was observed that CHWs have gaps in knowledge about DM and communication techniques, which limits their professional performance and the shared production of health care. Therefore, Continuing Health Profession Education proposals that address DM and communication techniques, such as MI, based on a dialogical, critical-reflective methodology that has meaning in the daily work of CHWs would greatly benefit these professionals and the people they follow. Therefore, Continuing Health Profession Education proposals that address DM and communication techniques such as MI, based on a dialogical, critical-reflective methodology, with theoretical-practical activities that have meaning in the daily work of CHWs, would benefit especially these professionals and the people they support. Furthermore, other possibilities for overcoming the difficulties identified in this study are popular health education groups and regular spaces for supervision and knowledge sharing among the Family Health team. Based on the results of this research, we present, as a technical product of this professional master's degree, a training proposal for CHWs focusing on DM and MI.